Hybrid cascaded multilevel inverter with PWM control method - Haiwen Liu; Leon M. Tolbert; Surin Khomfoi; Burak Ozpineci; Zhong Du (My University, 2008)
A hybrid cascaded multilevel inverter with PWM method is presented in this paper. It consists of a standard 3-leg inverter (one leg for each phase) and H-bridge in series with each inverter leg. It can use only a single DC power source to supply a standard 3-leg inverter along with three full H-bridges supplied by capacitors. Multilevel carrier- based PWM method is used to produce a five-level phase voltage. The inverter can be used in hybrid electric vehicles (HEV) and electric vehicles (EV). A simulation model based on PSIM and MATLAB/SIMULINK is developed. An experimental 5 kW prototype inverter is built and tested. The results experimentally validate the proposed PWM hybrid cascaded multilevel inverter.
Keywords: H bridge; Grid-tie inverter; Multilevel Inverters and Converters